Leveraging the sugarcane CRISPR/Cas9 technique for genetic improvement of non-cultivated grasses - Li, Chunjia; Iqbal, Muhammad Aamir (Frontiers in Plant Science, 2024)
Under changing climatic scenarios, the fundamentals and management principles of grasslands conservation and development are evolvinghave become imperative to impart functional sustainability to their ecosystem services. These goals could not be effectively and efficiently achieved without targeted genetic improvement of native grass species. To the best of our literature search, very scant research findings are available pertaining to gene editing of unnon-cultivated grass species (switch grass, wild sugarcane, Prairie cordgrass, Bermuda grass, Chinese silver grass etc.) prevalent in natural and semi-natural grasslands. Thus, to explore this novel research aspect, this study purposes that gene editing techniques employed for improvement of cultivated grasses especially sugarcane might be used for non-cultivated grasses as well. Our hypothesis behind suggesting sugarcane as a model crop for non-cultivated grasses genetic improvement of non-cultivated grasses is the intricacy of gene editing owing to polyploidy and aneuploidy compared to other cultivated grasses (rice, wheat, barley, maize etc.). Another reason is genome editing protocols in sugarcane (x = 10-13), have been developed and optimized keeping in view high level of genetic redundancy. Thus, as per our knowledge, this review is the first study that objectively evaluates the concept and functioning of CRISPR/Cas9 technique in sugarcane regarding high versatility, target specificity, efficiency, design simplicity and multiplexing capacity in order to explore novel research perspectives for gene editing of non-cultivated grasses against biotic and abiotic stresses. Additionally, pronounced challenges confronting to sugarcane gene editing have resulted in the development of different variants (Cas9, Cas12a, Cas12b and SpRY) of CRISPR tool whose technicalities have also been critically assessed.